2019
DOI: 10.1177/0972262918821241
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Workplace Spirituality and Teacher Self-efficacy on Organizational Citizenship Behaviour of Secondary School Teachers: An Indian Scenario

Abstract: Research on workplace spirituality is on the rise primarily because of the win-win situation it creates for both employees and organizations. Spirituality at work has been associated with many individual-level work behaviour and attitudes. Also, self-efficacy is another significant construct which considerably affects individual work experiences. The current study focuses on the relationship between workplace spirituality, self-efficacy and organizational citizenship behaviour (OCB) in secondary school teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 64 publications
1
11
0
2
Order By: Relevance
“…However, the component of sense cannot explain it. These results are consistent with Norouzi et al [41], Wagner [18], Sachdeva [19], Pirkola et al [22], Ashmos & Duchon [26], Karakas [27], Milliman et al [29], Azad Marzabadi et al [31], Mahopalan [32,42], Masci et al [28] Faro [33], Pawar [34], Soha [24], Joelle [35], and Garg [36]. It is alsoin line with the results of Neal [37], Sintaasih Desak [38), Sony, and Mekoth [39] research.…”
Section: Discussionsupporting
confidence: 88%
“…However, the component of sense cannot explain it. These results are consistent with Norouzi et al [41], Wagner [18], Sachdeva [19], Pirkola et al [22], Ashmos & Duchon [26], Karakas [27], Milliman et al [29], Azad Marzabadi et al [31], Mahopalan [32,42], Masci et al [28] Faro [33], Pawar [34], Soha [24], Joelle [35], and Garg [36]. It is alsoin line with the results of Neal [37], Sintaasih Desak [38), Sony, and Mekoth [39] research.…”
Section: Discussionsupporting
confidence: 88%
“…Teachers with high self-efficacy believe that they have the abilities to perform their tasks, and are more likely to exhibit OCB voluntarily such as supporting their co-workers on work-related problems, staying back after formal teaching hours in assisting students to surpass in studies, and taking part in non-rewarded roles in school (Mahipalan et al, 2019;Oplatka, 2006). They restructure their working timetable to accommodate others and strive to adopt different innovative classroom instructional approaches (Beauregard, 2012).…”
Section: H2(a-c)mentioning
confidence: 99%
“…
Organisational citizenship behaviour entails the display of voluntary extra-role behaviours that are not formally paid for but are essential for organisational success (Katz, 1964;Organ, 1988). Generally, OCB has been found to be related to teacher efficacy and workplace spirituality (Choong, Ng, Ai Na, & Tan, 2019;Mahipalan & Muhammed, 2019) and reduced turnover intention (Risa & Purba, 2019). It has also been reported that OCB predicts quality, creativity and efficient performance (Yaakobi & Weisberg, 2020).
…”
mentioning
confidence: 99%